Molecular profile of pure squamous cell carcinoma of the bladder identifies major roles for OSMR and YAP signalling. (14th March 2022) - Hurst, Carolyn D; Cheng, Guo; Platt, Fiona M; Alder, Olivia; Black, Emma VI; Burns, Julie E; Brown, Joanne; Jain, Sunjay; Roulson, Jo‐An; Knowles, Margaret A
Abstract: Pure squamous cell carcinoma (SCC) is the most common pure variant form of bladder cancer, found in 2–5% of cases. It often presents late and is unresponsive to cisplatin‐based chemotherapy. The molecular features of these tumours have not been elucidated in detail. We carried out whole‐exome sequencing (WES), copy number, and transcriptome analysis of bladder SCC. Muscle‐invasive bladder cancer (MIBC) samples with no evidence of squamous differentiation (non‐SD) were used for comparison. To assess commonality of features with urothelial carcinoma with SD, we examined data from SD samples in The Cancer Genome Atlas (TCGA) study of MIBC. TP53 was the most commonly mutated gene in SCC (64%) followed by FAT1 (45%). Copy number analysis revealed complex changes in SCC, many differing from those in samples with SD. Gain of 5p and 7p was the most common feature, and focal regions on 5p included OSMR and RICTOR . In addition to 9p deletions, we found some samples with focal gain of 9p24 containing CD274 (PD‐L1). Loss of 4q35 containing FAT1 was found in many samples such that all but one sample analysed by WES had FAT1 mutation or deletion. Expression features included upregulation of oncostatin M receptor (OSMR), metalloproteinases, metallothioneins, keratinisation genes, extracellular matrix components, inflammatory response genes, stem cell markers, and immune response modulators. Exploration of differentially expressed transcription factors identified BNC1 and TFAP2A, a gene repressed by PPARG, as the most upregulated factors. Known urothelial differentiation factors were downregulated along with 72 Kruppel‐associated (KRAB) domain‐containing zinc finger family protein (KZFP) genes. Novel therapies are urgently needed for these tumours. In addition to upregulated expression of EGFR, which has been suggested as a therapeutic target in basal/squamous bladder cancer, we identified expression signatures that indicate upregulated OSMR and YAP/TAZ signalling. Preclinical evaluation of the effects of inhibition of these pathways alone or in combination is merited.